Carrying rocks: Hoarding behaviour in the Gravettian occupation of Cova Gran de Santa Linya (SE Pyrenees). (February 2022) - Sánchez-Martínez, Javier; Mora Torcal, Rafael; Martínez-Moreno, Jorge; Roda Gilabert, Xavier; Roy-Sunyer, Miquel
Highlights: Lithic resources can be accumulated as an effective subsistence strategy in response to times of stress. Hoards, caches and small-scale storages informs about foresighted mechanisms in the organization of human activities. Cova Gran de Santa Linya hoard comprises 27 chalcedony tested nodules, representing one of the few evidences of storing behaviour in Southwestern Europe. This assemblage allows amplifying the range of human responses within the social, technical and organizational sphere. Abstract: Lithic resources can be accumulated to form caches or hoards as an effective subsistence strategy in response to times of stress. Hoarding behaviour is the manifestation of foresighted mechanisms, and is one of the common and also little known strategies among forager groups. In this paper, we present the evidence of such behaviour: a deposit of raw material recovered from level 497C of the Cova Gran de Santa Linya (SE Pyrenees). The lithic hoard is made up of 27 chalcedony nodules that have been tested at the site and exhibit great variability in terms of size and shape. The geostatistical analysis applied to the accumulations of raw materials identified has allowed us to determine spatial relationships between different categories in the archaeological record, such as nodules and cores, and has yielded insight into the use of chalcedony in specific areas of the occupation. The archaeological data suggest that this stockpile of raw material functioned as small-scale storage, constituting one of the few references about hoarding behaviour during the Palaeolithic, and the first time it has been exhaustively described in the Gravettian on the Iberian Peninsula. The lithic hoard from the Cova Gran allows us to investigate the role played by raw material hoards in the planning of subsistence activities and the organisation of human occupations.